Distribution, Population Status and Ecology of the Endangered Barbary Macaque Macaca sylvanus in North Africa - Alami, Abderrazak El; Lavieren, Els Van; Ahmim, Mourad; Namous, Salwa; Fattah, Abderrazzak; Znari, Mohamed; Chait, Abderrahman (International Journal of Scientific Research in Biological Sciences, 2021)
The Barbary macaque Macaca sylvanus currently survives in small fragmented isolates in Morocco and Algeria. Between 65 and 75 % of the world’s population occurred in the central zone of the Moroccan Middle Atlas. In Morocco, the species survives today in the Rif, the Middle Atlas and the High Atlas mountains. In Algeria it occurs in three areas: Chiffa, Grande Kabylie and Petite Kabylie. Free-ranging Barbary macaques are currently found in Gibraltar. In Europe, there are three major free ranging captive colonies of Barbary macaques in France and Germany. In the early 1980s, the total population size was estimated to be 14 000–23 000. Several recent studies indicated a dramatic decline of the Barbary macaque populations and concluded this decline on habitat destruction, impact of livestock grazing, the population fragmentation, the illegal capture of infant macaques, and the effects of human activities on the Barbary macaques’ behaviour. The species is listed in CITES Appendix I and is classified as an endangered species on the IUCN’s Red List. Barbary macaques are an essential component of North Africa biodiversity, contributing to forest regeneration and ecosystem health. This paper aims to determine the current distribution, status and ecology of the Barbary macaque in Morocco and Algeria, to identify the potential threats to the species, and to make recommendations for the protection of the species in North Africa.